GNAQ Mutation in the Venous Vascular Malformation and Underlying Brain Tissue in Sturge–Weber Syndrome - Sundaram, Senthil K. (Neuropediatrics, 2017)
The recent identification of the somatic GNAQ mutation (c.548G > A) provides insight into the pathogenesis of Sturge–Weber syndrome (SWS). Although the primary SWS brain pathology is the leptomeningeal angiomatosis (LMA), cerebral cortical and white matter abnormalities play a prominent role in the disease manifestations. In some cases, SWS brain involvement is present even without detectable LMA on magnetic resonance imaging (MRI). To expand our understanding of the etiology of SWS brain pathology, surgical SWS brain specimens from nine children (age: 0.8–7.5 years) were carefully separated into LMA and (non-LMA) brain tissue; the latter did not contain any vascular malformation. A custom Competitive Allele-Specific TaqMan PCR (castPCR) assay to detect the mutation in GNAQ was performed in these separated specimens. The mutation was present in all nine LMA and seven of the nine non-LMA brain tissues. LMA tissues were significantly enriched by the mutation, as compared with non-LMA brain (mean: 7.2 ± 2.1% and 1.2 ± 0.4%, respectively; p = 0.008). These results demonstrate that the somatic GNAQ mutation in SWS is not confined to the venous vascular malformation but can directly (although less severely) affect underlying brain parenchyma, not directly affected by LMA, and possibly contribute to SWS brain pathology. Future studies should identify the specific cell type(s) affected by the mutation in the SWS-affected brain parenchyma.